What are the functionalities and features of mobile health record apps supporting persons experiencing social exclusion? A systematic literature review - Izaturwanaho, Felicien; Ward, Marie E.; Ní Cheallaigh, Clíona; Moran, Maeve; Fitzgerald, Geraldine; Mockler, David; Geary, Una; Corrigan, Siobhán (Frontiers in Digital Health, 2025)
BackgroundResearch into mobile health record apps has focused on narrow outcomes, such as medication adherence for persons experiencing chronic conditions. However, no review has examined their use in the context of social exclusion. Persons experiencing social exclusion (PESE) face complex health needs, limited healthcare access, and increased exposure to traumatic life experiences. It is imperative to consider a trauma-informed and integrated care approaches when developing an app for them, and they should be involved as key stakeholders to ensure equitable care. This review examined these apps’ functionalities and features that support PESE in relation to their reported outcomes and the delivery of a trauma-informed and/or integrated care.MethodsA systematic search of ten databases: Web of Science Core Collection, Medline, PsycINFO, CINAHL, Cochrane, Embase, Scopus, ProQuest Dissertations and Theses A&I, Lenus and OpenGrey International were undertaken, and was supplemented with non-indexed and grey literature. Searches were undertaken in April 2024 in English with no date limit, and used the PRISMA 2020 guidelines. Studies were deemed eligible if they met the SPIDER framework criteria.ResultsOne thousand three hundred and thirty-two papers were found eligible for the review, of which eleven qualified for inclusion following screening and quality assessment using QATSDD and MMAT tools. Four themes were found (supporting integrated and connected care; enhancement of user engagement and care coordination; improving data accuracy and access to care; and provision of ongoing monitoring and feedback) related to apps’ functionalities and features, which in turn were linked to reported outcomes. Although a few of these apps’ functionalities and features were aligned with the six principles of trauma-informed care, none of them were implemented considering a trauma-informed care and/or integrated care.ConclusionThis review provided insights into the complexities of implementing a mobile health record app for PESE. However, limited available data restricted a comprehensive understanding of these apps’ functionalities and features in their specific implementation settings in relation to their reported outcomes. Next steps include translating these findings into survey and interview questions to identify end-user requirements for developing an app for PESE from a trauma-informed perspective to promote integrated care.Systematic review registrationPROSPERO CRD42024535090.